DEVELOPMENT OF A TEAM GAMES TOURNAMEN MODEL BASED ON MULTILEVEL GAMES TO INCREASE THE MOTIVATION TO LEARN IPS OF STUDENTS - Wati, Arista; Kurniawan, Bayu; Rahayu, Linda Zulkifa; Pratama, Bima Wahyu; Sari, Erna (UNDIKMA, 2025)
The low motivation of students to learn in social studies subjects shows that the learning model applied is not fully in accordance with the learning needs of students. Learning motivation is one of the important factors that greatly influence the success of the learning process. Therefore, this research aims to develop a learning model that is able to increase student learning motivation through a learner-centered approach. This type of research is a development research (Research and Development) using the Design Thinking model, which consists of five main stages: Empathize, Define, Ideate, Prototype, and Test. The data collection techniques used include observation, interviews, diagnostic tests, and Likert scale questionnaires. While data analysis was carried out descriptively qualitative and quantitative. The product developed is a Team Games Tournament (TGT) learning model based on multilevel games, namely Sambung Kata, Tebak Gaya, and Family Hundred. This model was validated by experts and tested on students of class VIIF SMP Laboratorium UM. The results showed that this model is valid, very practical, and effective in increasing student learning motivation. The increase in student motivation is characterized by an increased awareness to participate in learning, the desire to achieve high grades, complete assignments on time, and high enthusiasm in participating in learning activities without feeling bored. Thus, this multilevel games-based TGT model can be an innovative alternative to increase student learning motivation in social studies subjects